Przekład artystyczny wobec funkcji dyskursu aksjologicznego w tekście źródłowym - Warchał, Mateusz (Przekłady Literatur Słowiańskich, 2012)
Translation process and function of axiological discourse in the source text The aim of presented discussion is an attempt to identify the function of discourse about values and its distribution in translated texts with an indication of the difficulties that accompany this process. Translation of axiological discourse hidden and explicit purpose of author’s evaluative reality — emotions, and their features make it functional in the secondary text. Translation is not absolute, even if the values are absolute. The discourse analyzed in the text and (re)presented in translation is a reflection of socially constructed network of meanings, perceptions and ways of narration, contributing to the “Balkan” social relations. On the basis of examples author shows how the implementation process takes place with the use of emotionally-moving language, which serve axiological valuation category and makes the practice of translation difficult. Key words: axiological discourse, translation, network of meanings, emotionally-moving language, categorization.